Association between dietary carotenoids intake and chronic constipation in American men and women adults: a cross-sectional study - Jiangnan Wang; Wanru Kong; Min Liu; Yuping Wang; Ya Zheng; Yongning Zhou (BMC, 2023)
Abstract Background Dietary carotenoids have been proven to improve intestinal disorders like inflammatory bowel disease and colon cancer, yet little is known about the link between dietary carotenoids and constipation. This study aims to examine the relationship between dietary carotenoids intake and constipation, using data from the National Health and Nutrition Examination Survey (NHANES) 2005-2010. Methods A total of 11,722 participants were enrolled. Chronic constipation was defined as type 1 (separate hard lumps, like nuts) and type 2 (sausage-like, but lumpy) in the Bristol stool form scale (BSFS). Carotenoids intake was obtained from the average of two 24-hour dietary recall questionnaires (if only one 24-hour was available, we used it) and divided into quartiles (Q). The prevalence of constipation was calculated across men and women individuals. The relationship between dietary carotenoids intake and constipation in men and women was assessed with weighted logistic regression and smoothed curve fitting after adjusting confounders, with results displayed as weighted odds ratio (OR) with 95% confidence intervals (95% CI). The model was further stratified by age, race, and HEI 2015 scores (with median as cutoff) among men and women. Results The total weighted prevalence of chronic constipation in this study was 8.08%, 11.11% in women and 5.18% in men. After multivariable adjustment, compared with the lowest intake, participants with the highest dietary lycopene intake (ORQ4 vs. Q1= 0.55, 95% CI: 0.36-0.84, p for trend = 0.01) and total lycopene intake (ORQ4 vs. Q1 = 0.52, 95% CI: 0.34-0.80, p for trend = 0.01) were negatively associated with the risk of chronic constipation in men, whereas increased dietary α-carotene intake reduced the risk of chronic constipation in women (ORQ4 vs. Q1 = 0.69, 95% CI: 0.48-0.98, p for trend = 0.04). Smoothing curve fitting further supported these results and provided evidence of dose-response effects. No association was found between other types of carotenoids and chronic constipation in men and women. Conclusions Increasing lycopene intake may improve bowel function in men while increased α-carotene intake may reduce the risk of chronic constipation in women. Further studies are essential to explore the role that the intake of carotenoids plays in chronic constipation.